1991
DOI: 10.1007/bf01833352
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor (PDGF) in plasma of breast cancer patients: Correlation with stage and rate of progression

Abstract: Plasma levels of platelet-derived growth factor (PDGF) were measured in 58 female patients with breast cancer and in 9 normal female control subjects by means of a specific radioimmunoassay. Levels in normal control subjects were all below the lower limits of detection by the assay (1.56 fmol/100 microliters plasma). Two of 17 (12%) patients with stage 2 breast cancer had detectable plasma levels. Among patients with Stage 4 breast cancer 13/41 (32%) had significantly elevated levels (greater than 2 times the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 31 publications
1
52
0
2
Order By: Relevance
“…Our present finding suggests that PDGF is also released by melanomas in vivo, although we cannot exclude the possibility that PDGF present in cyst fluid is derived from cells other than melanoma proper, such as endothelial cells. The association of increased plasma PDGF levels with advanced metastatic spread of breast carcinomas, without concomitant platelet abnormalities, has been reported (Ariad et al, 1991). Leitzel et al (1991) also reported that cancer patients had increased plasma PDGF levels.…”
Section: Discussionmentioning
confidence: 88%
“…Our present finding suggests that PDGF is also released by melanomas in vivo, although we cannot exclude the possibility that PDGF present in cyst fluid is derived from cells other than melanoma proper, such as endothelial cells. The association of increased plasma PDGF levels with advanced metastatic spread of breast carcinomas, without concomitant platelet abnormalities, has been reported (Ariad et al, 1991). Leitzel et al (1991) also reported that cancer patients had increased plasma PDGF levels.…”
Section: Discussionmentioning
confidence: 88%
“…The median number of treatment cycles was three (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in the 20 evaluable patients ( Table 2). Fifteen (75%) discontinued treatment because of progressive disease and five (25%) discontinued treatment because of adverse events, including: grade 3 headache (n ϭ 1), grade 3 transaminitis (n ϭ 1), grade 2 dyspepsia and weight loss (n ϭ 1), grade 3 headache, hypertension, and chest pain (n ϭ 1), and grade 3 gastrointestinal hemorrhage (n ϭ 1).…”
Section: Treatmentmentioning
confidence: 99%
“…A number of key proangiogenic factors, including vascular endothelial growth factor (VEGF) and its receptors (VEGFRs) [4,5] and the class III receptor tyrosine kinases platelet-derived growth factor receptor (PDGFR) [6,7] and stem cell factor receptor (KIT), are overexpressed in breast cancer [8 -10]. Many of these are associated with a poor prognosis [11][12][13][14] and a poor response to systemic chemotherapy in advanced breast cancer patients [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Two of the cases with serum elevation also had increased tissue expression, suggesting that the tumors were the source of the serum proteins. Another study reported elevated serum erbB-2 ECD by ELISA (defined as greater than 2 (51,52). In addition, in this study, there were 7 cases of in situ carcinoma without invasion, and 3 of these (43%) had elevated serum ECD levels, suggesting that this may be a biomarker of early malignant disease in certain cases of breast cancer.…”
Section: Oncoproteins Growth Factor Receptorsmentioning
confidence: 46%
“…Levels were greater than the highest control value of 0.69 ng/ml in 19 (15%) of the cases, although, based on other markers, in only 5 (4%) of the cases was the tumor felt to be the source of the growth factor. Plasma PDGF levels have also been determined by radioimmunoassay (RIA) in 58 breast cancer patients and 9 normal female controls (2). All of the controls were below the lower limit of detection of the assay (1.56 fmol/100 1l), but 20 of 17 (12%) stage II cancer patients had detectable levels and 13 of 41 (32%) stage IV cancer patients had elevated levels (defined as more than twice the lower limit of detection of the assay).…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%